2020
DOI: 10.1038/s41416-020-01190-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel staging system integrating the number and location of lymph nodes for gastric adenocarcinoma

Abstract: Background Evidence suggests that the anatomic extent of metastatic lymph nodes (MLNs) affects prognosis, as proposed by alternative staging systems. The aim of this study was to establish a new staging system based on the number of perigastric (PMLN) and extra-perigastric (EMLN) MLNs. Methods Data from a Chinese cohort of 1090 patients who had undergone curative gastrectomy with D2 or D2 plus lymphadenectomy for gastric cancer were retrospectively analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Li et al . 23 reported that PLNM and ELNM showed prognostic values independent of the extent of gastrectomy and defined one extragastric metastatic LN as equivalent to ~2.6 perigastric metastatic LNs in terms of the degree of influence on prognosis. Some scholars have attempted to integrate the anatomical position and amount of metastatic LNs into a new LN staging system 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al . 23 reported that PLNM and ELNM showed prognostic values independent of the extent of gastrectomy and defined one extragastric metastatic LN as equivalent to ~2.6 perigastric metastatic LNs in terms of the degree of influence on prognosis. Some scholars have attempted to integrate the anatomical position and amount of metastatic LNs into a new LN staging system 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…1, 2, 3, 4, 5, and 6) and extragastric lymph node metastasis (ELNM, No. 7, 8, 9, 10, 11, and 12) may prompt the distinguished values for GC prognostic evaluation 23 . At present, we aim to establish a comprehensive prognostic model for accurate prognostic evaluation based on ELNM and LNR in node-positive GC after curative surgery.…”
Section: Introductionmentioning
confidence: 99%